Corporate Governance and Environmental Policies of Global Hotels - S. Dahab; Santos, M-C. (4th International Conference on Multinational Enterprises and Sustainable Development MESD 15, 2015)
Corporate governance has been much debated in the last decades due to its impact on stakeholders’ wealth and, ultimately, on socio-economic development. Most studies have targeted large, quoted corporations operating mainly in manufacturing, trade or finance. Despite its size and specificity, only scant attention has been paid to the hotel industry. Previous research has focused on organizational choices, neglecting most other governance issues. This paper analyses secondary data on six of the largest hotel chains, searching for the link between governance choices and geographical spread. Our findings suggest that different home regions translate into substantial differences across these variables. European chains are heavily influenced by language and cultural factors, selecting regions that mimic the host country’s characteristics. By contrast, emerging Asian and Latin American chains are more geographically bounded, while American chains prefer light entry modes such as franchising. Older hotel groups are more prone to adopting “good governance practices” but the difference with emerging groups from Asia is not very large. We also find that hotel chains have been increasing their efforts and concerns with sustainability and environmental issues.